A study on the factors influencing performance of Islamic Real Estate Investment Trust (REIT) in Malaysia / Noorfarahin Sedek - Sedek, Noorfarahin (Faculty of Business and Management, 2018)
This study examines the connection between Stock Market Price (KLCI), Inflation Rate (CPI), Interest Rate (INT), Gross Domestic Product (GDP) towards performance of Islamic REITs in Malaysia from year 2007 to 2016 for quarterly data. This study employs time series data with total of 40 observations. The data had been examined by using Ordinary Least Square (OLS), Descriptive analysis, Unit Root test, linear regression which consists of single linear regression and multiple linear regression as well as Diagnostic test in order to determine the existence of error terms in a data. The result shows that Stock Market Price, Inflation Rate and Gross Domestic Product are significant connection with performance of Islamic REITs. However, Interest Rate is not significant connection with performance of Islamic REITs.